Identification of Arhgef12 and Prkci as genetic modifiers of retinal dysplasia in the Crb1rd8 mouse model. - Sonia M Weatherly; Gayle B Collin; Jeremy R Charette; Lisa Stone; Nattaya Damkham; Lillian F Hyde; James G Peterson; Wanda Hicks; Gregory W Carter; Jürgen K Naggert; Mark P Krebs; Patsy M Nishina (PLoS Genetics, 2022)
Mutations in the apicobasal polarity gene CRB1 lead to diverse retinal diseases, such as Leber congenital amaurosis, cone-rod dystrophy, retinitis pigmentosa (with and without Coats-like vasculopathy), foveal retinoschisis, macular dystrophy, and pigmented paravenous chorioretinal atrophy. Limited correlation between disease phenotypes and CRB1 alleles, and evidence that patients sharing the same alleles often present with different disease features, suggest that genetic modifiers contribute to clinical variation. Similarly, the retinal phenotype of mice bearing the Crb1 retinal degeneration 8 (rd8) allele varies with genetic background. Here, we initiated a sensitized chemical mutagenesis screen in B6.Cg-Crb1rd8/Pjn, a strain with a mild clinical presentation, to identify genetic modifiers that cause a more severe disease phenotype. Two models from this screen, Tvrm266 and Tvrm323, exhibited increased retinal dysplasia. Genetic mapping with high-throughput exome and candidate-gene sequencing identified causative mutations in Arhgef12 and Prkci, respectively. Epistasis analysis of both strains indicated that the increased dysplastic phenotype required homozygosity of the Crb1rd8 allele. Retinal dysplastic lesions in Tvrm266 mice were smaller and caused less photoreceptor degeneration than those in Tvrm323 mice, which developed an early, large diffuse lesion phenotype. At one month of age, Müller glia and microglia mislocalization at dysplastic lesions in both modifier strains was similar to that in B6.Cg-Crb1rd8/Pjn mice but photoreceptor cell mislocalization was more extensive. External limiting membrane disruption was comparable in Tvrm266 and B6.Cg-Crb1rd8/Pjn mice but milder in Tvrm323 mice. Immunohistological analysis of mice at postnatal day 0 indicated a normal distribution of mitotic cells in Tvrm266 and Tvrm323 mice, suggesting normal early development. Aberrant electroretinography responses were observed in both models but functional decline was significant only in Tvrm323 mice. These results identify Arhgef12 and Prkci as modifier genes that differentially shape Crb1-associated retinal disease, which may be relevant to understanding clinical variability and underlying disease mechanisms in humans.